Development Method for Determining the Law of Indonesian Ulama Council (MUI) Post Reform (Case Study of Fatwas related to Law) - Zul Anwar Ajim Harahap; Dame Siregar (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
This study aims to analyze the development of the method of determining the law by the Indonesian Ulama Council after the reformation in the case of legal fatwas. Data collection was carried out by way of interviews with MUI administrators throughout Indonesia represented by the fatwa commission which produced fatwas related to crucial issues of public interest and political fatwas that greatly influenced the political situation in Indonesia. The location of this research was conducted at the Central MUI institutions, DKI Jakarta Province, West Java Province, East Java Province, and West Sumatra. The results obtained are that the method used by the MUI runs in accordance with established procedures and standards in the MUI and does not shift from the previous period. The legal determination carried out by MUI has a special style compared to other institutions, namely a more moderate process, meaning that it is not extreme or radical. In setting a fatwa decision, the MUI is not influenced by political pressures from outside that surround it even though the pressure has a psychological impact on the perpetrators of the implementation of the law. The determination even though it looks like there is pressure, but in reality it is the response of the MUI itself. This is evidenced from several cases of MUI fatwa related to the needs of many people who are able to meet the sense of community law